The nitric oxide donor JS-K sensitizes U87 glioma cells to repetitive irradiation. Issue 6 (June 2017) - Heckler, Max; Osterberg, Nadja; Guenzle, Jessica; Thiede-Stan, Nina Kristin; Reichardt, Wilfried; Weidensteiner, Claudia; Saavedra, Joseph E; Weyerbrock, Astrid
As a potent radiosensitizer nitric oxide (NO) may be a putative adjuvant in the treatment of malignant gliomas which are known for their radio- and chemoresistance. The NO donor prodrug JS-K (O2-(2.4-dinitrophenyl) 1-[(4-ethoxycarbonyl) piperazin-1-yl] diazen-1-ium-1, 2-diolate) allows cell-type specific intracellular NO release via enzymatic activation by glutathione-S-transferases overexpressed in glioblastoma multiforme. The cytotoxic and radiosensitizing efficacy of JS-K was assessed in U87 glioma cells in vitro focusing on cell proliferation, induction of DNA damage, and cell death. In vivo efficacy of JS-K and repetitive irradiation were investigated in an orthotopic U87 xenograft model in mice. For the first time, we could show that JS-K acts as a potent cytotoxic and radiosensitizing agent in U87 cells in vitro. This dose- and time-dependent effect is due to an enhanced induction of DNA double-strand breaks leading to mitotic catastrophe as the dominant form of cell death. However, this potent cytotoxic and radiosensitizing effect could not be confirmed in an intracranial U87 xenograft model, possibly due to insufficient delivery into the brain. Although NO donor treatment was well tolerated, neither a retardation of tumor growth nor an extended survival could be observed after JS-K and/or radiotherapy.